Antifungal activity of Streptomyces spp. isolated from rhizosphere of Thai medicinal plants - Sutthinan Khamna (2018)
A collection of Streptomyces isolates from the rhizosphere of sixteen medicinal plants was assessed for in vitro antagonistic activity against six plant pathogenic fungi; Alternaria brassicicola, A. porri, Colletotrichum gloeosporioides, Fusarium oxysporum, Penicillium digitatum and Sclerotium rolfsii. Twenty-seven isolates showed activity against at least one of them. Streptomyces spectabilis CMU-PA101 recovered from soil associated with pandanus palm (Pandanus amaryllifolius) was very effective in producing bioactive metabolites against the six test fungi used in the screening test. The culture filtrate of strain CMU-PA101 was extracted using various solvents (chloroform, n-butanol, diethyl ether, ethyl acetate, and n-hexane). The n-butanol extract demonstrated the highest activity against the test organisms, with a minimum inhibitory concentration (MIC) of 0.781 to 6.250 mg/ml. The culture filtrate of this strain was effective against A. porri on Allium ascalonicum L (shallot) in greenhouse conditions. ©IJIB, All rights reserved.